Nutrition of the micropropagated fruit trees in vitro and ex vitro - Balla, I.; Vértesy, J.; Végváry, Gy.; Szűcs, E.; Kállay, T.; Vörös, I.; Bíró, B. (International Journal of Horticultural Science, 2003)
Some experience or details are introduced in connection with the nutrient uptake of micropropagated fruit trees in the different phase of the in vitro or ex vitro development. It can be stated, that the plants during the micropropagation procedure are overfed. Special careful nutrient supply is necessary during the acclimatization.